Intensity Of Drug Consumption In Inpatients In Therapeutic Communities Of The Ecuadorian Austro - Sánchez, Dolores Amparito Rodríguez; López-Sánchez, Dr. Carmen; García-Castillo, Dr. Fernando (Migration Letters, 2024)
Introduction: The intensity of the consumption of narcotic substances constitutes a serious social problem that affects the quality of life of those who consume them consecutively, with implications for physical and mental health. It is important to approach it from an informative and preventive perspective to understand the associated risks and promote healthy decisions. Objective: Identify the intensity of drug consumption in inpatients in Therapeutic Communities of Southern Ecuador. Methodology: A quantitative descriptive association study was carried out, the sample was non-probabilistic, 480 inmates, an express questionnaire prepared by the researcher was applied to collect the sociodemographic variables that allow characterizing the population and the drug consumption detection test. alcohol, tobacco and substances (ASSIST), for the analysis contingency tables and the Chi-square technique were used, the significance level α=0.05 was selected for the investigation. Results: It is shown that the variables age, sex, origin, education, marital status, occupation, economic income and length of confinement, with respect to the intensity of consumption of tobacco, alcohol, coca, tranquilizers, hallucinogens and opiates, for all cases The level of significance (p) (0.00) is less than 0.05, therefore the null hypothesis is rejected and the alternative hypothesis is accepted that the variables are dependent and there is a significant relationship between them. Conclusions: The consumption of substances such as alcohol, tobacco, coca, tranquilizers, hallucinogens and opiates in all consumer patients is dependent on sociodemographic variables and is significantly associated.